Isogenic iPSC-derived CTBP1 mutant neuronal cells exhibit neurodevelopmental defects - Lee, Suhjin; Vijayalingam, Selvamani; Klotz, Elliott; Dedert, Cass; Xu, Fenglian; Chinnadurai, Govindaswamy; Ezekiel, Uthayashanker R. (Frontiers in Neuroscience, 2025)
Hypotonia, ataxia, developmental delay, and tooth enamel defects syndrome (HADDTS) is a recently identified disorder linked to a heterozygous mutation in the C-terminal Binding Protein 1 (CTBP1) transcriptional corepressor. The predominant mutation (p.R342W) is located within the major protein binding cleft (PXDLS), crucial for CtBP1’s interaction with transcriptional regulatory proteins. To investigate the mutation’s functional consequences, we generated isogenic induced pluripotent cell lines (iPSCs) carrying the CTBP1 mutation in heterozygous and homozygous conditions using the CRISPR/Cas9 editing method. The transcriptional profile of iPSC-derived early neurons from the isogenic wild type and CTBP1 heterozygous and homozygous mutants was determined by genome-wide RNA sequencing. The RNA-Seq data revealed downregulation of several key transcription factors, with homozygous mutations causing more pronounced downregulation compared to heterozygous mutations. Isogenic mutant neural stem cells (NSCs) exhibited reduced adhesion and migration, along with dysregulated calcium signaling, while mutant neurons showed premature neurite outgrowth. Together, our transcriptomic and biological results provide novel insights into the role and mechanism of CTBP1 p.R342W mutation in the defective neurodevelopmental processes.